Investigation of drying pumpkin slices by low-pressure superheated steam - Sittiritkawin P. (2017)
This paper aims to investigate the use of low-pressure superheated steam (LPSS) drying for pumpkin slices. The experiments were conducted at the drying temperatures of 80°C-120°C and absolute pressures of 7-40 kPa to examine the drying kinetics, quality of dried products viz. color, shrinkage, rehydration, microstructure, texture (hardness and crispness) and β-carotene degradation, and the specific energy consumption(SEC) of the process. Results showed that drying at higher temperature and lower pressure reduced the drying time and SEC, except at pressures of 30-40 kPa. Page's equation was used to describe the drying kinetics, in which its kinetic parameters were expressed as a function of drying conditions. Higher drying temperature resulted in lower shrinkage, better rehydration and texture whereas pressure had no obvious effect on almost all quality, however, lower pressure provided better β-carotene retention. Furthermore, the product color was not obviously affected by these drying conditions. LPSS drying at 120°C and 7 kPa was proposed as the most favorable condition for drying pumpkin slices.